Self-repairing rubber foaming material capable of being reprocessed and recycled

By introducing dynamic ester bonds and supercritical nitrogen foaming technology into rubber materials, the problem of difficult traditional rubber materials to heal and recycle is solved, and efficient self-healing, excellent mechanical properties and good recycling performance are achieved, which meets the requirements of green chemistry and sustainable development.

CN119798811AActive Publication Date: 2025-04-11QINGDAO UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510027431.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Due to the stability of the covalent crosslinking network, traditional rubber materials are difficult to heal or recycle and reprocess, which limits their development potential in specific applications. The existing reversible crosslinking systems rely on specific chemical reactions or external conditions, and the stability and preparation process are complex.

Method used

Self-healing reprocessable and recyclable rubber foaming materials are prepared using dynamic ester bonds (formed by ring-opening reactions of epoxy groups and carboxylic acid groups in malic acid or citric acid) and supercritical nitrogen foaming technology.

Benefits of technology

It realizes efficient self-repair of materials after damage, maintains excellent mechanical properties, low-density foaming and good recycling and reprocessing performance, which is in line with the concept of green chemistry and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798811A_ABST
    Figure CN119798811A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing reprocessable and recoverable rubber foaming material, and relates to the technical field of rubber foaming materials, and the technical scheme is as follows: a rubber foaming material matrix is prepared by mixing components such as an epoxidized natural rubber matrix, a reversible cross-linking agent, a filler and the like and adopting a vulcanization process. A supercritical foaming technology is used for foaming treatment, and a reprocessing material is recycled through a hot pressing and refoaming technology. Efficient self-repairing is achieved by introducing dynamic ester bonds, and the service life can be remarkably prolonged. By optimizing the formula, the self-repairing performance and the mechanical strength are balanced, and the durability of the material is enhanced. And a supercritical nitrogen foaming technology is adopted, the low-density material is successfully prepared, and the lightweight characteristic is improved. The material has excellent recovery performance, and can be reprocessed for multiple times through hot pressing and supercritical foaming processes. By combining a biomass cross-linking agent and a green process, the material conforms to green chemistry and sustainable development concepts and has relatively low environmental influence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber foam materials, and in particular to a self-repairing, reprocessable and recyclable rubber foam material. Background Art

[0002] Due to its excellent elasticity, processability and physical and mechanical properties, rubber materials are widely used in transportation, aerospace, construction and other fields, and have become one of the most widely used categories of polymer materials. The excellent properties of rubber materials have made them widely demanded in modern industry. However, in order to improve the mechanical strength, durability and service life of rubber materials, traditional cross-linking systems, such as sulfur vulcanization system and peroxide vulcanization system, are widely used. These cross-linking systems can effectively promote the formation of high-bond energy covalent cross-linking networks between rubber molecular chains, thereby improving the mechanical properties and heat resistance of rubber. However, the stability of this covalent cross-linking network also makes it difficult to break or reorganize during use, so that traditional rubber materials cannot self-heal or be recycled and reprocessed when damaged, which greatly limits its development potential in some specific applications. With the increasing requirements of modern society for environmental protection and sustainable development, especially in the recycling and reprocessing of waste rubber, how to develop new rubber materials with both good mechanical properties and self-healing and recycling capabilities has become a research hotspot in the field of materials science.

[0003] In recent years, research on dynamic cross-linked rubber materials has made significant progress. In 2011, Professor Leibler's team introduced ester bonds as cross-linking bonds in the epoxy resin system and successfully prepared a "glass-like" material with self-healing and reprocessing capabilities, ushering in a new era of self-healing and recyclable thermosetting materials. Since then, more and more researchers have begun to pay attention to how to introduce dynamic covalent bonds into rubber materials to give the materials self-healing and recycling capabilities. For example, researchers use dynamic covalent bond structures such as disulfide bonds, β-hydroxy ester bonds, and imine bonds, and use external stimuli (such as heat, light, pH, etc.) to achieve the breaking and recombination of these bonds, thereby making the rubber material have self-healing and recyclable properties.

[0004] Although some progress has been made in the research of self-healing and recyclable rubber materials, the existing technology still has significant shortcomings. First, most of the existing reversible cross-linking systems rely on specific chemical reactions or external conditions (such as high temperature, acid-base environment, etc.), which may lead to reduced stability of the material or complex preparation process, limiting its large-scale application. For example, although the cross-linking system based on disulfide bonds or ester bonds can provide better self-healing effects, its cross-linking process and reaction conditions are relatively harsh, and in the long-term use process, the self-healing ability of the material may gradually decrease with repeated damage repair. In addition, although supercritical fluid foaming technology has been proven to be able to effectively reduce environmental pollution and has been applied in some high-end fields, its application in reversible cross-linked rubber materials is still relatively rare, and it has not been able to fully realize its potential in the preparation of lightweight and environmentally friendly rubber foam materials.

[0005] In the current technology, the research on the self-healing and recycling ability of rubber materials still faces many challenges, especially how to improve the recycling and reprocessing performance of materials, reduce production costs and achieve environmentally friendly treatment under the premise of meeting the material performance requirements, which is still an urgent problem to be solved. In addition, how to prepare lightweight and recyclable rubber materials with reversible cross-linking structure and environmentally friendly foaming technology without relying on special conditions such as high temperature is still an important research direction.

[0006] Therefore, solving these technical problems, especially developing green rubber materials that can maintain high mechanical properties and have excellent self-healing and recycling capabilities, is the key to research in this field. Current research urgently needs to overcome the limitations of existing technologies, especially in the synergistic improvement of self-healing and recycling performance, and propose more innovative and efficient solutions. Summary of the invention

[0007] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a self-repairing, reprocessable and recyclable rubber foam material matrix, wherein the rubber foam material matrix is ​​prepared from the following raw materials in mass fraction:

[0008] 80-100 parts of epoxidized natural rubber matrix, 2-6 parts of reversible crosslinking agent, 5-30 parts of filler, 2-6 parts of 1,2-dimethylimidazole, 2-4 parts of zinc stearate, 5-10 parts of n-octyl terephthalate and 2 parts of antioxidant.

[0009] Preferably, the epoxidized natural rubber matrix is ​​epoxidized natural rubber or a blend of epoxidized natural rubber and other polymers, the mass ratio of epoxidized natural rubber is 70%-100%, and the other polymer is one of polybutylene succinate and ethylene-vinyl acetate copolymer.

[0010] Preferably, the epoxidation degree of the epoxidized natural rubber is 25%-50%.

[0011] Preferably, the reversible crosslinking agent is either malic acid or citric acid.

[0012] Preferably, the filler is one of carbon black, white carbon black, lignin and carboxymethyl cellulose.

[0013] Preferably, the antioxidant is one or both of antioxidant 2246 and antioxidant 1010.

[0014] The present invention also provides a method for preparing the self-repairing, reprocessable and recyclable rubber foam material matrix as mentioned above, the preparation method comprising: mixing 80-100 parts of an epoxidized natural rubber matrix, 2-6 parts of a reversible crosslinking agent, 5-30 parts of a filler, 2-6 parts of 1,2-dimethylimidazole, 2-4 parts of zinc stearate, 5-10 parts of n-octyl terephthalate and 2 parts of an antioxidant at a mixing temperature of 50-120°C to obtain a rubber mix, and then vulcanizing the rubber mix at a vulcanization temperature of 160°C for 20-60 minutes to obtain the rubber foam material matrix.

[0015] The present invention also provides a method for preparing a self-repairing, reprocessable and recyclable rubber foam material, comprising the following steps:

[0016] A1 puts the rubber foam material matrix into a supercritical foaming device to remove the air in the device;

[0017] A2 is saturated with nitrogen;

[0018] A3 is heated to the foaming temperature, and after the reaction is completed, the pressure is released to room temperature to obtain the rubber foam material.

[0019] The rubber foam material matrix is ​​prepared by the above-mentioned preparation method.

[0020] Preferably, the nitrogen pressure in step A2 is 15-30 MPa, and the saturation time is 2-6 h.

[0021] Preferably, in step A3, the foaming temperature is 80-110°C.

[0022] The present invention also provides a method for recycling a self-repairing, reprocessable and recyclable rubber foam material, comprising the following steps:

[0023] B1 crushing the rubber foam material and hot pressing at 180°C for 60-120min to obtain the recycled material;

[0024] B2 placing the recycled material in a supercritical foaming device at a foaming temperature of 80-140° C. and 15-30 MPa nitrogen conditions, saturating for 2-6 hours and then foaming to obtain a recycled foaming material;

[0025] The rubber foam material is prepared by the above-mentioned preparation method.

[0026] The technical solution provided by the present invention brings beneficial effects:

[0027] Excellent self-healing performance: By introducing dynamic ester bonds (formed by ring-opening reactions between epoxy groups and carboxylic acid groups in malic acid or citric acid), the rubber foam material provided by the present invention can achieve relatively efficient self-repair after damage occurs. The repair efficiency of the sample of the present invention can reach up to 89.2% within 2 hours, which greatly improves the service life of the material. The realization of this self-healing effect stems from the reversibility of dynamic ester bonds. They can break at the site of damage and recombine through external conditions (such as temperature, pressure, etc.) to restore the mechanical properties of the material. This mechanism ensures the effective repair of the material after multiple damages, thereby extending the service life and solving the problem that traditional covalent cross-linked materials cannot self-heal.

[0028] Excellent mechanical properties: The prepared material exhibits high tensile strength, with the highest tensile strength of the sample reaching 15.162MPa. By adjusting the ratio of the reversible crosslinker and the formula of other additives, the present invention can achieve the best balance between the mechanical properties and self-healing ability of the material. This technical effect not only enhances the strength of the material through the introduction of dynamic ester bonds, but also improves its durability in practical applications.

[0029] Low density and good foaming performance: Using supercritical nitrogen as a foaming agent, the present invention successfully prepared a low-density rubber foam material with a foam density as low as 0.118g / cm 3 , significantly improving the lightweight characteristics of the material. Low density not only reduces the weight of the material, but also makes it possible to be used in a variety of lightweight structural applications, in line with the concept of green chemistry and sustainable development. Supercritical fluid foaming technology uses the good solubility and diffusivity of nitrogen in a supercritical state to ensure the uniformity and stability of the foam structure, while avoiding the environmental pollution problems that may be caused by traditional chemical foaming methods.

[0030] Good recycling and reprocessing performance: The rubber foam material of the present invention has excellent recycling and reprocessing capabilities. Through simple hot pressing and supercritical foaming processes, the material can still maintain good physical properties after multiple heat treatments and foaming. Specifically, after hot pressing at 180°C for 60-120 minutes, the material can be recycled and further processed through supercritical foaming to maintain good foaming characteristics. This recycling method not only improves the resource utilization efficiency of the material, but also reduces the generation of waste, which is in line with the principles of green chemistry and circular economy.

[0031] Green and sustainable: By using biomass materials malic acid or citric acid as a cross-linking agent and combining it with supercritical fluid foaming technology, the rubber foam material provided by the present invention realizes a production process with low environmental impact. Malic acid and citric acid, as chemical substances of natural origin, not only reduce the dependence on petroleum-based resources, but also make the final product more environmentally friendly. Compared with traditional rubber foam materials, the materials of the present invention can be reused through a simple recycling method, which greatly improves the sustainability of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the SEM image of Example 3 of the present invention;

[0033] Figure 2 This is the SEM image of Example 4 of the present invention;

[0034] Figure 3 This is the SEM image of Example 5 of the present invention;

[0035] Figure 4 This is a physical picture of Example 3 of the present invention; a is a rubber foam material, b is a crushed rubber foam material, and c is a stretched strip-shaped rubber material after recovery. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0037] Example 1

[0038] Preparation of a self-repairing, reprocessable and recyclable rubber foam material matrix: 100 parts of epoxidized natural rubber with an epoxidation degree of 50%, 2 parts of malic acid, 10 parts of white carbon black, 2 parts of 1,2-dimethylimidazole, 4 parts of zinc stearate, 10 parts of n-octyl terephthalate and 2 parts of antioxidant 2246 are mixed at a mixing temperature of 50°C to obtain a rubber mixture, and then the rubber mixture is vulcanized at a vulcanization temperature of 160°C for 30 minutes to obtain the rubber foam material matrix.

[0039] Preparation of self-healing reprocessable and recyclable rubber foam materials:

[0040] A1 puts the rubber foam material matrix into a supercritical foaming device to remove the air in the device;

[0041] A2 was saturated with nitrogen at a pressure of 20 MPa and a saturation time of 2 h.

[0042] A3 is heated to 80°C, and after the reaction is completed, the pressure is released to room temperature to obtain the rubber foam material.

[0043] Self-healing reprocessable and recyclable rubber foam material recycling:

[0044] B1 crushes the rubber foam material and hot presses it at 180°C for 120min to obtain the recycled material;

[0045] B2: placing the recycled material in a supercritical foaming device at a foaming temperature of 80°C and 20MPa nitrogen conditions, saturating for 2h and then foaming to obtain a recycled foaming material.

[0046] Embodiment 2-10

[0047] The same preparation method as in Example 1 was used for preparation, except that the above were as shown in Tables 1 and 2.

[0048] Comparative Example 1-2

[0049] The same preparation method as in Example 1 was used for preparation, except that the above was as shown in Table 3.

[0050] Table 1 Example Conditions List

[0051]

[0052]

[0053] Table 2 Example Conditions List

[0054]

[0055] Table 3 Comparative Example Conditions

[0056]

[0057]

[0058] Experimental test:

[0059] 1. Mechanical properties: Cut the material and its foamed samples into dumbbell-shaped tensile specimens and use an electronic universal testing machine to perform tensile tests at room temperature with a test speed of 500 mm / min. Test 5 samples under each set of process conditions and calculate the average value.

[0060] 2. Structure and morphology: The fracture morphology of the material samples was observed using a scanning electron microscope (SEM, JSM-7610FPULS). The samples were fractured in liquid nitrogen and mounted on a platform with a conductive adhesive film. Then the cross-section was sprayed with gold three times with a current of 3ma, each time for 60s. ImageJ software was used to calculate the micropore diameter in the sample SEM image.

[0061] 3. Self-repair rate: The ratio of the tensile strength before and after self-repair is used to represent the self-repair efficiency. Self-repair efficiency η = σ / σ0, where σ is the tensile strength after self-repair and σ0 is the tensile strength before self-repair.

[0062] Table 4 Experimental data summary

[0063]

[0064]

[0065] Self-repair performance: From the experimental data, the self-repair rates of Examples 1 to 10 are all high, which shows that after damage occurs, the material can restore its mechanical properties more efficiently, achieving the technical effect of the present invention - excellent self-repair performance. Comparative Experiment 1 and Comparative Experiment 2 both show a lack of self-repair ability and cannot be repaired. This shows that traditional rubber foam materials lack a dynamic ester bond self-repair mechanism and cannot achieve recovery after material damage, proving the unique advantages of the present invention in self-repair.

[0066] Mechanical properties: Example As the filler and cross-linking agent change, the tensile strength gradually increases, showing that the present invention can balance the relationship between self-repairing ability and mechanical strength by adjusting the cross-linking agent ratio and adding different additives. The comparative experiment shows that the mechanical properties of the traditional material are relatively high, but due to its lack of self-repairing function, it cannot provide the comprehensive advantages of the material of the present invention. In particular, although comparative experiment 1 has a higher strength, it cannot be repaired, indicating that its damage resistance is poor.

[0067] Density and foaming performance: The examples show that the density of the materials varies with the formulation. Overall, the foaming density of the examples is relatively low, which indicates that the present invention can effectively reduce the weight of the materials through supercritical foaming technology, meeting the requirements of low density and good foaming performance. Comparative Experiment 2 is a relatively low-density material, but the material lacks durability because it cannot self-repair. Although Comparative Experiment 1 has a better foaming effect, it also exhibits poor overall performance because it cannot be repaired.

[0068] Reprocessing performance: The materials of all embodiments can be reprocessed and foamed, and maintain good physical properties. The change in foaming density after reprocessing shows that the material has good recycling and reprocessing performance. This technical effect ensures the recyclability of the material through hot pressing and supercritical foaming processes, and can still maintain good foaming characteristics after multiple heat treatments. Comparative Experiment 1 and Comparative Experiment 2 both failed to achieve reprocessing and foaming, and could not meet the requirements of recycling and reprocessing, indicating that the recycling and processing performance of traditional materials after use is poor, and cannot be compared with the materials of the present invention in terms of environmental protection and sustainability.

[0069] Green and sustainable: The present invention can effectively reduce the dependence on traditional petroleum-based resources and reduce the environmental impact of the production process by using a cross-linking agent of natural origin (malic acid or citric acid) and supercritical fluid foaming technology. The reprocessability and recyclability of the material are demonstrated in the examples, which is in line with the principles of green chemistry and circular economy. Although the materials in the comparative experiments have certain foaming ability and mechanical properties, their shortcomings of being unable to be repaired and recycled make them not meet the requirements of sustainable development.

[0070] The SEM images of the embodiments show that as the amount of cross-linking agent increases, the degree of cross-linking of the material increases, the pore size of the foaming material decreases, the number of pores decreases, and correspondingly the density of the foaming material increases, and the self-repairing efficiency decreases.

[0071] The present invention uses an innovative dynamic ester bond self-repairing mechanism, combined with supercritical fluid foaming technology and green environmentally friendly materials, to successfully achieve efficient self-repairing, excellent mechanical properties, low-density foaming and good recycling and reprocessing performance, and has broad application prospects and sustainable development advantages.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-repairing, reprocessable and recyclable rubber foam material matrix, characterized in that: The rubber foam material matrix is ​​prepared from the following raw materials in mass fraction: 80-100 parts of epoxidized natural rubber matrix, 2-6 parts of reversible crosslinking agent, 5-30 parts of filler, 2-6 parts of 1,2-dimethylimidazole, 2-4 parts of zinc stearate, 5-10 parts of n-octyl terephthalate and 2 parts of antioxidant.

2. The self-repairing, reprocessable and recyclable rubber foam material matrix according to claim 1, characterized in that: The epoxidized natural rubber matrix is ​​epoxidized natural rubber or a blend of epoxidized natural rubber and other polymers, the mass ratio of epoxidized natural rubber is 70%-100%, and the other polymer is one of polybutylene succinate and ethylene-vinyl acetate copolymer.

3. The self-repairing, reprocessable and recyclable rubber foam material matrix according to any one of claim 2, characterized in that: The epoxidation degree of the epoxidized natural rubber is 25%-50%.

4. The self-repairing, reprocessable and recyclable rubber foam material matrix according to claim 1, characterized in that: The reversible cross-linking agent is either malic acid or citric acid.

5. The self-repairing, reprocessable and recyclable rubber foam material according to claim 1, characterized in that: The filler is one of carbon black, white carbon black, lignin and carboxymethyl cellulose, and the antioxidant is one or two of antioxidant 2246 and antioxidant 1010.

6. A method for preparing a self-repairing, reprocessable and recyclable rubber foam material matrix as claimed in claims 1-5, characterized in that: The preparation method comprises the following steps: mixing 80-100 parts of an epoxidized natural rubber matrix, 2-6 parts of a reversible crosslinking agent, 5-30 parts of a filler, 2-6 parts of 1,2-dimethylimidazole, 2-4 parts of zinc stearate, 5-10 parts of n-octyl terephthalate and 2 parts of an antioxidant at a mixing temperature of 50-120° C. to obtain a rubber mix; and then vulcanizing the rubber mix at a vulcanization temperature of 160° C. for 20-60 minutes to obtain the rubber foam material matrix.

7. A method for preparing a self-repairing, reprocessable and recyclable rubber foam material, characterized in that: The following steps are involved: A1 puts the rubber foam material matrix into a supercritical foaming device to remove the air in the device; A2 is saturated with nitrogen; A3 is heated to the foaming temperature, and after the reaction is completed, the pressure is released to room temperature to obtain the rubber foam material. The rubber foam material matrix is ​​prepared by the preparation method described in claim 6.

8. The method for preparing the self-repairing, reprocessable and recyclable rubber foam material according to claim 7, characterized in that: The nitrogen pressure in step A2 is 15-30 MPa, and the saturation time is 2-6 h.

9. The method for preparing the self-repairing, reprocessable and recyclable rubber foam material according to claim 7, characterized in that: In the step A3, the foaming temperature is 80-110°C.

10. A method for recycling a self-repairing, reprocessable and recyclable rubber foam material, characterized in that: The following steps are involved: B1 crushing the rubber foam material and hot pressing at 180°C for 60-120min to obtain the recycled material; B2 placing the recycled material in a supercritical foaming device at a foaming temperature of 80-140° C. and 15-30 MPa nitrogen conditions, saturating for 2-6 hours and then foaming to obtain a recycled foaming material; The rubber foam material is prepared by the preparation method described in claim 7.

Citation Information

Patent Citations

  • Method for vulcanizing nitrile elastomer

    CN102134325A

  • Rubber sealing gasket for capacitor and preparation method of rubber sealing gasket

    CN103627118A

  • High-viscosity self-repair non-curing waterproof coating material

    CN109535803A

  • Epoxy functionalized rubber crosslinked elastomer with repeatable processability and preparation method of elastomer

    CN110642964A

  • Wide-temperature-range damping rubber material and preparation method thereof

    CN117001863A